2019
DOI: 10.1016/j.ijheatmasstransfer.2019.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Topology optimization as a powerful tool to design advanced PEMFCs flow fields

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 90 publications
0
50
0
1
Order By: Relevance
“…Only the Navier-Stokes equations are approximated by FEM, while the Lagrangian transport is modelled cross-section-wise. Behrou et al [106] presented a density-based approach for the design of proton exchange membrane fuel cells using a depth-averaged two-dimensional approximation of reactive porous media flow. Chen et al [107] extended their previous work [104] to three-dimensional problems.…”
Section: Species Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the Navier-Stokes equations are approximated by FEM, while the Lagrangian transport is modelled cross-section-wise. Behrou et al [106] presented a density-based approach for the design of proton exchange membrane fuel cells using a depth-averaged two-dimensional approximation of reactive porous media flow. Chen et al [107] extended their previous work [104] to three-dimensional problems.…”
Section: Species Transportmentioning
confidence: 99%
“…However, some works directly approximate a three-dimensional plane problem, with a small thickness, using a two-dimensional simplification, either stated explicitly [43,64,67,68,106,112,116,134,140,142,143,149] or implicitly [50,67,87,102,107]. Out of these, only three papers [106,140,143] include the viscous resistance from the friction due to the out-of-plane viscous boundary layers. This is despite the fact that a simple expression is given in the original works on the subject [7,8].…”
Section: D Simplification Of 3dmentioning
confidence: 99%
“…Originating in PEFCs, Guo et al 178 created leaf-like ow elds emulating the venous, biological structure found in plants and blood vessels. Employing a topological optimisation, Behrou et al 179 proposed a depth-averaging model to maximise power density in PEFCs. The topological optimisation procedure has taken root in RFBs as a numerical study; 180 however, the performance of many of these ow eld designs has yet to be experimentally validated.…”
Section: Electrolyte Ow Eld Effectsmentioning
confidence: 99%
“…The performance and life of the HT‐PEMFC stack are much lower than that of the LT‐PEMFC stack, which is mainly caused by poor consistency of the HT‐PEMFC stack at present . The factors that affect the HT‐PEMFC stack consistency are numerous, among which the uniformity of the flow distribution within the cell and between cells is very important …”
Section: Specific Conditions Of the Testmentioning
confidence: 99%
“…The performance and life of the HT-PEMFC stack are much lower than that of the LT-PEMFC stack, which is mainly caused by poor consistency of the HT-PEMFC stack at present. [3][4][5][6] The factors that affect the HT-PEMFC stack consistency are numerous, among which the uniformity of the flow distribution within the cell [7] and between cells is very important. [8,9] Most of the research on flow distribution between cells focuses on numerical simulation, which is mainly related to the influence of the structure parameters and operating parameters of manifolds on flow distribution in the stack.…”
mentioning
confidence: 99%